Recombineering: Genetic Engineering in Escherichia coli Using Homologous Recombination. Issue 2 (13th February 2023) - Thomason, Lynn C.; Costantino, Nina; Li, Xintian; Court, Donald L.
Abstract: The bacterial chromosome and bacterial plasmids can be engineered in vivo by homologous recombination using either PCR products or synthetic double‐stranded DNA (dsDNA) or single‐stranded DNA as substrates. Multiple linear dsDNA molecules can be assembled into an intact plasmid. The technology of recombineering is possible because bacteriophage‐encoded recombination proteins efficiently recombine sequences with homologies as short as 35 to 50 bases. Recombineering allows DNA sequences to be inserted or deleted without regard to the location of restriction sites and can also be used in combination with CRISPR/Cas targeting systems. © 2023 Wiley Periodicals LLC. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA. Basic Protocol : Making electrocompetent cells and transforming with linear DNA Support Protocol 1 : Selection/counter‐selections for genome engineering Support Protocol 2 : Creating and screening for oligo recombinants by PCR Support Protocol 3 : Other methods of screening for unselected recombinants Support Protocol 4 : Curing recombineering plasmids containing a temperature‐sensitive replication function Support Protocol 5 : Removal of the prophage by recombineering Alternate Protocol 1 : Using CRISPR/Cas9 as a counter‐selection following recombineering Alternate Protocol 2 : Assembly of linear dsDNA fragments into functional plasmids Alternate Protocol 3 : Retrieval of alleles onto a plasmid by gap repair Alternate Protocol 4 : Modifying multicopy plasmids with recombineering Support Protocol 6 : Screening for unselected plasmid recombinants Alternate Protocol 5 : Recombineering with an intact λ prophage Alternate Protocol 6 : Targeting an infecting λ phage with the defective prophage strains